Targeted mutagenesis of the CYP79D1 gene via CRISPR/Cas9-mediated genome editing results in lower levels of cyanide in cassava - Juma, Bicko Steve; Mukami, Asunta; Mweu, Cecilia; Ngugi, Mathew Piero; Mbinda, Wilton (Frontiers in Plant Science, 2022)
Cassava is the world's most essential food root crop, generating calories to millions of Sub-Saharan African subsistence farmers. Cassava leaves and roots contain toxic quantities of the cyanogenic glycoside linamarin. Consumption of residual cyanogens results in cyanide poisoning due to conversion of the cyanogens to cyanide in the body. There is a need for acyanogenic cassava cultivars in order for it to become a consistently safe and acceptable food, and commercial crop. In recent years, the CRISPR/Cas system, has proven to be the most effective and successful genome editing tool for gene function studies and crop improvement. In this study, we performed targeted mutagenesis of the MeCYP79D1 gene in exon 3, using CRISPR/Cas9, via Agrobacterium-mediated transformation. The vector design resulted in knockout in cotyledon-stage somatic embryos regenerated under hygromycin selection. Eight plants were recovered and genotyped. DNA sequencing analysis revealed that the tested putative transgenic plants carried mutations within the MeCYP79D1 locus, with deletions and substitutions being reported upstream and downstream of the PAM sequence, respectively. The levels of linamarin and evolved cyanide present in the leaves of mecyp79d1 lines were reduced up to seven-fold. Nevertheless, the cassava linamarin and cyanide were not completely eliminated by the MeCYP79D1 knockout. Our results indicate that CRISPR/Cas9-mediated mutagenesis is as an alternative approach for development of cassava plants with lowered cyanide content.